15 Organic psychosis: using electronic patient records to investigate demographics, aetiology and outcome. Issue 8 (13th July 2017) - Misselbrook, Thomas; Patel, Rashmi; Nicholson, Tim; Cullen, Alexis; Pollak, Tom
Abstract : Objective: Organic psychosis (OP) is where psychosis is due to an identified medical illness and have been considered separately from nonorganic psychotic (NP) disorders. Despite being a clinically important topic with different treatment options and healthcare pathways very little is known about OP in terms of prevalence, the relative frequency of causes and whether it differs from nonorganic psychoses in terms of key clinical variables such as demographics, symptomatology and outcomes. Furthermore there is growing criticism of the potentially artificial distinction between OP and NP. The objective was to investigate the occurrence and demographics of patients with OP as well as type and duration of hospital admission. Aetiology and characterisation of symptoms within medical sub-categories was also investigated, with the aim of updating the literature at a scale previously not undertaken. Method: We conducted an observational electronic case register study using an anonymised dataset of over 2 50 000 patients from the South London and Maudsley NHS Trust (SLaM) Biomedical Research Centre (BRC). Results: OP accounted for 553 cases (3%) of a total of 18 297 psychosis patients. Dementia, epilepsy and infectious and inflammatory disorders were the most common causes of OP. As expected, high rates of visual hallucinations were found in OP, particularly in patients with movement disorders (75%), cerebrovascular disease (75%) and dementia (65%). High rates of auditory hallucinations were found in patients with cerebral trauma (55%), epilepsy (50%) and infectious and inflammatory disorders (35%). Paranoid delusions were reported most commonly in patients with dementia (50%), infectious and inflammatory disorders (45%) and movement disorders (40%). OP patients were 12 years older at diagnosis (p<0.001), more likely to be female (p<0.01) and twice as likely to be white (p<0.001) compared to NP. They were also less likely to have a long stay (>30 days) and were less likely to be detained under the Mental Health Act (p<0.001). Furthermore, patients with OP were 38% less likely to have multiple admissions (>2) and had significantly (p<0.001) fewer documented alcohol and drug problems, worse cognitive problems and worse physical illness scores. Conclusion: These novel findings characterise, with an unprecedented sample size, an under-researched but clinically important diagnosis. These data suggests OP is relatively rare but more common in female and white patients although it is not known if this is due to differences in aetiological risk factors, e.g. inflammatory disorders, or other reasons such as variation in rates of investigation and diagnosis. Differences in hospitalisation rates and outcome suggest differences in effective treatment between groups. It has been proposed that a large proportion, and possibly even all, psychoses are in fact organic and is increasingly important to research this relatively neglected group, particularly to ensure early detection and, where appropriate, aetiologically specific treatment.